Misterium śmierci wg "Prognosticum Futuri Saeculi" Juliana z Toledo - Kasprzak, Dariusz Antoni; Zbroja, Bogdan (Vox Patrum, 2025)
Julian of Toledo's Prognosticum futuri saeculi is a treatise that tackles the profound enigma of human death. This issue is of existential and eschatological significance for all of us, yet the full scope of the eschatological thought of the thirty-first Bishop of Toledo (who held office from 380-390) remains shrouded in mystery, including his views on death. We have traced Julian's thoughts on the mystery of death, commented on them and determined whether they stem from the biblical text or are more of a religious inference made on the basis of Christian tradition.We concluded that Julian's description of the mysterium mortis follows from the truths of the Christian faith, contained in the public revelation given to the Church in biblical revelation and in the revelation of Church Tradition. Julian's view is that death is a consequence of human sin and represents the separation of the soul from the body. However, he does not fear it, since for believers it is a cleansing from sins and an exit to meet Christ in eternity.This is not an original thought, as Msgr. Toledo is based primarily on the theological theses of the earlier Church Fathers (mainly Augustine of Hippo and Cyprian of Carthage). In Prognosticum futuri saeculi liber I, he uses theological argumentation in twenty-one of the twenty-two theses. In only one does the argumentation strictly come from Scripture; when Bishop Toledo refers to the text of Scripture, it is to justify a previously stated thesis from Tradition. Julian's skill lies in the structure of the treatise itself; he presents a concise and straightforward catechesis on the idea that Christians should not fear death, though it occasionally comes across as overly simplistic and didactic.